Study on Prediction of Sluice Settlement Based on Improved GM (1,1) Model - LI Xuede; ZHOU Mingming; ZHAO Jinlei; LIU Yang; JIANG Wenzhi; WANG Guizhi (Renmin Zhujiang)
In the settlement monitoring,the amount of initial monitoring data is little with great changes.It can effectively enhance the correlation of the data series and improve the accuracy of the model through pre-processing the data and modeling with GM prediction model.In view of the single value of weight coefficient in the traditional GM prediction model,this paper selects the optimal weight coefficient for the establishment of the GM prediction model by introducing superimposed weight coefficients and changing the initial value.The results show that the improved GM prediction model with high accuracy can accurately predict the actual measured value.